Textural optimization of Ledre: Indonesian crepes-like snack - Kiki Fibrianto; Sri Hastuti; Harijono Harijono; Erni Sofia Murtini; Aly Akbar (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Ledre is a traditional crepes-like snack uniquely made by Indonesian Chinese descendant in Bojonegoro, East Java, Indonesia. However, there is a lot of varieties in terms of formulations, ingredients and techniques. Therefore, this study aimed to optimize the composition of raw materials (comparison of rice flour and tapioca, thickness of coconut milk with the ratio of coconut and water (w/v) and the amount of banana addition) using the response surface method (RSM) to optimize the textural quality of Ledre. It was found that the optimum textural quality of Ledre obtained with a ratio of rice flour: tapioca of 17.5: 1, a ratio of water and coconut milk of 4: 1 and the addition of 4 g bananas. This Ledre was characterized by 428.18 gf of fracturability value, 600.22 gf of hardness, 3.31% of water content, 5.03% of protein content, 1.73% of ash content, 5.27% of fat content, and 43.48 of brightness (L*).